The Parent trap - Meyers, Nancy (Pasig City : Viva Video, 1999)
What if you spent your whole life wishing for something you didn't know you already had? Hallie Parker and Annie James are about to find out. From Walt Disney Pictures and the creators of Father of the Bride Comes the hilariously fresh and contemporary retelling of the classic hit THE PARENT TRAP. Hallie is cool girl from California . Annie is a fair rose from London. When the two accidentally meet at summer camp, they think they have nothing in common except... they're identical twins (both played by LINDSAY LOHAN! Now they're up to their parents (DENNIS QUAID and NATASHA RICHARDSON) back together and have the family they're always wished for! This charming, heartwarming and delightfully clever comedy adventure will enchant your entire family.